ALTERNATIVE INCOME CONTRIBUTION OUT OF FISHERY IN SUPPORTING FISHERMAN HOUSEHOLDS IN KALANGAN VILLAGE PANDAN SUB-DISTRICT CENTRAL TAPANULI REGENCY NORTH SUMATERA PROVINCE - Nasution, Adnan Ripai; Darwis, Darwis; Bathara, Lamun (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTThis research was conducted on February 2020 which took place in Kalangan Village, Pandan Sub-District, Central Tapanuli Regency, North Sumatra Province.. The aim of this research was calculating the amount of fishermen household income obtained from fishing and alternative businesses and calculating the contribution of alternative businesses and analyzing the influence of the socio-economic characteristics of fishermen in Kalangan Village on the contribution of fishermen household alternative businesses..This study used a survey method, namely direct observation of objects in the field and data collection and the sampling method was random sample samplingFrom the results of the research conducted, the total household income in fisheries was IDR 3,002,200 while the total household income outside fisheries is IDR 1,757,633, The contribution that was contributed from non-fishery business was, 37% while from fishery business was 63% and it shows that the factors (variables) that influence the contribution of fishermen household are age and working hours, while education, experience work, the number of dependents has no influence on the contribution of fishermen household income.Keywords: Contribution, Alternative Income, Fishermen